Severe radiographic knee osteoarthritis - does Kellgren and Lawrence grade 4 represent end stage disease? - the MOST study - Guermazi, Ali; Hayashi, D.; Roemer, Frank; Felson, D. T.; Wang, K.; Lynch, John; Amin, S.; Torner, J.; Lewis, C. E.; Nevitt, M. C. (Osteoarthritis and Cartilage, 2015)
To determine what MRI-detectable osteoarthritis features that are not visualized on radiography demonstrate progression longitudinally in Kellgren and Lawrence (KL) grade 4 knees.We studied subjects from the Multicenter Osteoarthritis Study who had KL grade 4 knees at baseline and had baseline and 30-month MRI. Cartilage damage, bone marrow lesions (BMLs), meniscal damage, synovitis (signal changes in Hoffa fat pad), and effusion (fluid equivalent signal in the joint cavity) were semiquantitatively scored using the Whole Organ MRI Score (WORMS) system in five subregions of the medial and lateral tibiofemoral (TF) compartments. Analysis was performed for the compartment showing bone-on-bone appearance ("index") on radiograph and also for the other TF compartment of the same knee. Synovitis and effusion were assessed for the whole knee. Changes in scores at follow-up were noted for each feature. For cartilage and BML, within-grade changes were also recorded.140 subjects (164 knees) were included (50% women, mean age 66.0 ± 8.6 years, mean BMI 30.4 ± 5.1 kg/m(2)). Longitudinally, 51 index compartments (34%) showed an increase in the sum of cartilage scores from all subregions. In the other compartment, 25% showed an increase in the sum score for cartilage damage. For BMLs in the index compartment, 50 knees (33%) showed an increase in maximum score and 32 (21%) showed a decrease. Meniscal status mostly remained stable. Effusion worsened in 36 knees (25%) and improved in 13 knees (9%). Synovitis worsened in 14 knees (10%) and improved in six knees (4%).In KL grade 4 knees, MRI-detected cartilage loss and fluctuation of BMLs, effusion, and synovitis occurred frequently over a 30-month period.
EVALuna2:14526